To solve the equation \( 2x - 5 = 3(4x + 5) \), you can follow these steps in order:
-
Distribute on the right side: Multiply both terms inside the parentheses by 3. \[ 2x - 5 = 12x + 15 \]
-
Rearrange the equation: Move all terms involving \( x \) to one side and constant terms to the other side. This can be done by subtracting \( 12x \) from both sides: \[ 2x - 12x - 5 = 15 \] or simplified as: \[ -10x - 5 = 15 \]
-
Isolate the term with \( x \): Add 5 to both sides of the equation. \[ -10x = 20 \]
-
Solve for \( x \): Divide both sides by -10. \[ x = -2 \]
So the ordered steps to solve the equation \( 2x - 5 = 3(4x + 5) \) are:
- Distribute on the right side.
- Rearrange the equation to isolate the \( x \) terms.
- Isolate the term with \( x \) on one side.
- Solve for \( x \).